Hubungan Kelelahan dengan Kepatuhan Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis di Rumah Sakit Sentra Medika Minahasa Utara - Karinda, Keren Bethany Onibala; Wantania, Frans Erwin Nicolaas; Wirawan, Alfonsius Ade (Mapalus Nursing Science Journal, 2025)
Background: Hemodialysis is the primary therapy used to remove metabolic waste from the blood in patients with chronic kidney disease (CKD). Although hemodialysis is crucial for the survival of CKD patients, the procedure has several physical impacts, one of which is fatigue. This fatigue can contribute to low adherence to the prescribed hemodialysis regimen. Objective: This study aimed to determine the relationship between fatigue and adherence in chronic kidney disease patients undergoing hemodialysis. Methods: This research used a quantitative approach with a cross- sectional design. The sample consisted of 137 hemodialysis patients selected using purposive sampling. Results: Based on the statistical analysis using Spearman’s rho correlation test, the result showed a p-value of 0.019 (p < 0.05), indicating a significant relationship between fatigue and adherence. The correlation coefficient was r = -0.200, which indicates a weak negative correlation. This means that the higher the level of fatigue experienced by patients, the lower their adherence tends to be. Conclusion: There is a significant relationship between fatigue and adherence in chronic kidney disease patients undergoing hemodialysis at Sentra Medika Hospital, North Minahasa. Keywords: Fatigue, Adherence, Chronic Kidney Disease, Hemodialysis.